Socialization of the Dangers of Doping and Addictive Substances on the Health and Performance of Young Athletes at AAFI Jayapura - Pamungkas Yulian Effendi; Fachrun Nisa Sofiyah Khasanah; Swandika Pinem; Abdul Bashir Nur Hasani; Muhammad Fitrah Muabarak (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Doping and the use of addictive substances pose a serious threat to the health and continued performance of athletes, including young futsal athletes from the Indonesian Futsal Association (AAFI) in Jayapura. The lack of structured anti-doping education leaves young athletes vulnerable to misinformation and at risk of using banned substances as a shortcut to performance enhancement.Aims: This community service activity aimed to increase the understanding of young AAFI Jayapura athletes regarding the dangers of doping and addictive substances to health and sports performance.Methods: The sample size for this study was 40 AAFI athletes. The test instrument used in this study was a Likert-scale questionnaire to determine the athletes' understanding of doping. The activity was carried out in four stages, namely preparation, educational implementation, evaluation and monitoring, as well as reporting and follow-up.Results: The results of the activity showed an increase in the average knowledge score from 28.29 (53.75%) in the pretest to 40.76 (77.45%) in the posttest, or an increase of 12.47 points (23.70%).Conclusion: This improvement demonstrates the effectiveness of direct education-based outreach in increasing young athletes' understanding of the types, health impacts, and consequences of doping and addictive substances. This activity is expected to serve as a model for sustainable educational interventions for other sports organizations in their efforts to support clean sport practices and develop young athletes who are physically, mentally, and ethically healthy.